Hypertrophy of the synovial membrane with the background of juvenile idiopathic arthritis under the mask of tenosynovial giant cell tumour: a clinical case report - Bespalova, Vladyslava; Petelytska, Liubov (The Ukrainian Scientific Medical Youth Journal, 2025)
juvenile idiopathic arthritis is the most common childhood rheumatologic disorder, characterized by chronic inflammation in the synovial joints. Its pathophysiology includes synoviocyte proliferation, pathological angiogenesis, and immune cell infiltration, leading to joint destruction and functional impairment. Tenosynovial giant cell tumor, a rare benign tumor affecting synovial tissues, often mimics juvenile idiopathic arthritis symptoms, complicating diagnosis. This case presents a 30-year-old male with a long history of juvenile idiopathic arthritis and recurrent uveitis, who was diagnosed with bilateral villonodular synovitis in the knee joints. Despite magnetic resonance imaging findings suggesting tenosynovial giant cell tumor, histopathological examination following knee arthroscopy revealed chronic moderate synovitis, confirming juvenile idiopathic arthritis pathology. The patient had not received disease-modifying antirheumatic drugs for several years, contributing to disease progression. The American College of Rheumatology highlights the importance of early disease-modifying antirheumatic drugs use, particularly methotrexate, to prevent joint damage in juvenile idiopathic arthritis. Delayed initiation of biologic disease-modifying antirheumatic drugs leads to poorer long-term outcomes, emphasizing the need for early intervention to control inflammation and prevent irreversible joint damage. This case underscores the diagnostic challenge of distinguishing juvenile idiopathic arthritis-related synovial hypertrophy from tenosynovial giant cell tumor and emphasizes the critical role of histopathological confirmation.